Perampanel outcomes at different stages of treatment in people with focal and generalized epilepsy treated in clinical practice: Evidence from the PERMIT study - Liguori, Claudio; Santamarina, Estevo; Strzelczyk, Adam; Rodríguez-Uranga, Juan Jesús; Shankar, Rohit; Rodríguez-Osorio, Xiana; Auvin, Stéphane; Bonanni, Paolo; Trinka, Eugen; McMurray, Rob; Sáinz-Fuertes, Ricardo; Villanueva, Vicente (Frontiers in Neurology, 2023)
The PERMIT study is the largest pooled analysis of perampanel (PER) clinical practice data conducted to date. This post-hoc analysis of PERMIT investigated the effectiveness, safety and tolerability of PER when used as early add-on therapy (after failure of one or two previous antiseizure medications) in comparison with late add-on therapy (after failure of three or more previous antiseizure medications). Retention and effectiveness were assessed after 3, 6, and 12 months, and at the last visit (last observation carried forward). Effectiveness was assessed by seizure type (total seizures, focal seizures, generalized tonic-clonic seizures [GTCS]) and assessments included seizure freedom rate and responder rate. Safety and tolerability were assessed by evaluating adverse events (AEs) and discontinuation due to AEs. The Full Analysis Set included 1184 and 2861 PWE treated with PER as early and late add-on therapy, respectively. Compared to the late add-on subgroup, the early add-on subgroup was characterized by later mean age at epilepsy onset, shorter mean duration of epilepsy, lower rates of intellectual disability and psychiatric comorbidity, and lower frequency of seizures per month, suggesting a less severe form of epilepsy in this subgroup. After 12 months, retention was significantly higher in the early versus late add-on subgroup (67.7% vs. 62.4%; p=0.004). At the last visit, responder rates in the early versus late add-on subgroup were significantly higher for total seizures (68.2% vs. 39.3%; p<0.001), focal seizures (65.0% vs. 36.8%; p<0.001) and GTCS (83.7% vs. 67.2%; p<0.001), as were seizure freedom rates (total seizures, 35.9% vs. 11.9% [p<0.001]; focal seizures, 29.4% vs. 8.7% [p<0.001]; GTCS, 69.0% vs. 48.1% [p<0.001]). Incidence of AEs was significantly lower in the early versus late add-on subgroup (42.1% vs. 54.7%; p<0.001), as was the rate of discontinuation due to AEs over 12 months (15.0% vs. 18.1%; p=0.031). This study demonstrated that PER was effective and generally well tolerated when initiated as early or late add-on therapy, but it was significantly more effective and better tolerated when initiated early. These findings support the use of PER as a broad-spectrum, early add-on therapy for use in PWE with focal and generalized seizures.